Loss aversion in sequential auctions - Antonio Rosato (Theoretical Economics, 2023)
I analyze sequential auctions with expectations-based loss-averse bidders who have independent private values and unit demand. Equilibrium bids are history dependent and subject to a discouragement effect: the higher the winning bid in the current round is, the less aggressive the bids of the remaining bidders in the next round. Moreover, because they experience a loss in each round in which they fail to obtain an object, bidders are willing to pay a premium in order to win sooner rather than later. This desire to win earlier leads prices to decline in equilibrium. I also show how various disclosure policies regarding the outcome of earlier auctions affect equilibrium bids, and that sequential and simultaneous auctions are neither bidder-payoff equivalent nor revenue equivalent.
Keywords: D03; D44; D81; D82; 330; afternoon effect; Loss aversion; sequential auctions